The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s1980-65742015000400002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of attitudes toward physical activity and sports

Abstract: Attitude is one of the most important predictor variables in relation to behavioral intentions regarding physical activity. Thus, this study aims to determine the influence of attitudes towards physical activity. The study comprised a sample of 1129 individuals (507 men and 622 women) age between 12 and 58 years ( = 18 sd = 4.03). To collect the data, the Scale of Attitudes Towards Physical Activity and Sports (Dosil, 2002) was based on the Portuguese version (Cid, Alves, & Dosil, 2008). The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
(17 reference statements)
1
4
0
1
Order By: Relevance
“…The same outcomes were obtained in different studies that revealed a decline in attitude scores as students progressed in grade level [5]. Thus, attitudes towards physical ac-tivity and sports are more positive in younger individuals [6,8,14,16,18,29,[32][33][34][35]. With regard to that, Lazarević et al [26] compared the attitudes of students in the 6 th , 7 th , and 8 th grades towards physical education, and Mercier et al [2] compared attitudes between the 4 th , 5 th , 6 th , 7 th , and 8 th grades.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The same outcomes were obtained in different studies that revealed a decline in attitude scores as students progressed in grade level [5]. Thus, attitudes towards physical ac-tivity and sports are more positive in younger individuals [6,8,14,16,18,29,[32][33][34][35]. With regard to that, Lazarević et al [26] compared the attitudes of students in the 6 th , 7 th , and 8 th grades towards physical education, and Mercier et al [2] compared attitudes between the 4 th , 5 th , 6 th , 7 th , and 8 th grades.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, despite students' attitudes being related to the teacher's personality, there are other factors that can influence their attitudes -namely, the curriculum, as well as the student's socio-economic status, ethnic group, gender, and age [8]. Research has also shown that students' attitudes toward physical education are more positive among males than in females, and among those who practice sports outside of school than in those who do not; also, attitudes towards physical education tend to become more negative as age increas-es [5,14,18,19]. Thus, to increase positive attitudes toward physical education, Fairclough and Stratton [20] studied the contribution of physical education to young people's physical activity levels; they argued that physical education classes may offer a logical and plausible context for regular participation in physical activity because school may provide a background for regular and structured physical activity participation.…”
Section: Introductionmentioning
confidence: 99%
“…Em um contexto onde existe a necessidade de produção, também vale a reflexão sobre um cenário de competitividade entre as revistas que recebem artigos da atividade física e saúde. Mesmo que a RBAFS se constitua como a revista mais relacionada ao tema, é reconhecido que artigos potenciais do tema atividade física e saúde também são publicados em outras revistas científicas nacionais de outras especialidades, como, por exemplo, Saúde Coletiva/Saúde Pública, Epidemiologia, Educação Física, Pediatria [12][13][14][15] . E esse nos parece ser um ponto que merece atenção, uma vez que a falta de indexação em bases de dados eletrônicas de maior porte e a baixa classificação do periódico no sistema Qualis-CAPES tornam a RBAFS menos competitiva em relação às outras opções, nem sempre se configurando como primeira opção para a submissão a = apresentação das cinco variáveis mais frequentes de manuscritos que comunicam pesquisas relacionadas ao tema atividade física e saúde.…”
Section: Discussionunclassified
“…Examining 1,129 individuals aged 12–58; Araújo and Dosil investigated how attitudes influence behavioral intentions for physical activity. Results indicated that younger males without higher education exhibit more favorable attitudes towards physical activity and sports compared to females ( 48 ). In another investigation involving middle school student, it was found that males exhibited a greater inclination towards engaging in physical activity compared to their female counterparts in terms of willingness to participate.…”
Section: Introductionmentioning
confidence: 95%